Analisis Diplomasi Digital Indonesia terhadap Negara-negara di Kawasan Afrika - Fetra Ardianto; Yokie Rahmad Isjchwansyah (Jurnal Ilmiah Hubungan Internasional, 2026)
This paper discusses Indonesia's digital diplomacy towards countries in the African region, emphasizing the use of Instagram as social media platforms by Indonesian diplomatic representatives. With qualitative approach, this research analyzes how Indonesia’s digital diplomacy supports efforts to promote national interests, strengthen bilateral relations, and enhance cooperation with African region countries. The research combines Digital Diplomacy Theory, PESTEL Analysis, and the Concept of Diplomatic Missions to evaluate Indonesia’s digital engagement. The findings reveal that the economic sector dominates Indonesia's digital diplomacy efforts compared to other sectors. Furthermore, the analysis shows that the “promoting” mission plays the most dominant role in Indonesia’s digital diplomacy towards African region countries. This research also highlights the importance of increasing digital activity by Indonesia’s newly established diplomatic representatives in the region and also expanding Indonesia's presence by establishing diplomatic representatives in other potential African region countries. This paper contributes to a deeper understanding of how digital diplomacy can be utilized to advance Indonesia’s foreign policy goals and strengthen its presence in emerging markets, particularly in the African region. Keywords: Digital Diplomacy; Indonesia; Africa; Social Media; Economy